Naissance et implantation de la Confédération générale du travail unitaire (1918-1927) - Charles, Jean (Annales littéraires, 2023)
The book traces the history of revolutionary trade unionism in the aftermath of the First World War, leading to the trade union split in the CGT and the birth of the CGTU. From the rise of the oppositionists to the confederal leadership, through the strikes of 1919-1920, it traces the genesis and beginnings of the CGTU in the post-war revolutionary context. The young CGTU is then studied in its structuring, its establishment and its particularlinks with the communist galaxy. The book ends in 1927 at the height of unitary trade unionism